Respuesta :
Answer:
Two solutions were found :
6x^2-x1=0
x = -1/3 = -0.333
x = 1/2 = 0.500
The solution of the equation 6x² - x - 1 = 0 are x = 1/2 and x = -1/3 after using the quadratic formula.
What is a quadratic equation ?
Any equation of the form [tex]\rm ax^2+bx+c=0[/tex] where x is variable and a, b, and c are any real numbers where a ≠ 0 is called a quadratic equation.
As we know, the formula for the roots of the quadratic equation is given by:
[tex]\rm x = \dfrac{-b \pm\sqrt{b^2-4ac}}{2a}[/tex]
We have a quadratic equation:
6x² - x - 1 = 0
Here a = 6, b = -1, c = -1
[tex]\rm x = \dfrac{-(-1) \pm\sqrt{(-1)^2-4(6)(-1)}}{2(6)}[/tex]
[tex]\rm x = \dfrac{1 \pm\sqrt{25}}{12}[/tex]
[tex]\rm x = \dfrac{1 \pm 5}{12}[/tex]
x = 6/12 = 1/2 or
x = -4/12 = -1/3
Thus, the solution of the equation 6x² - x - 1 = 0 are x = 1/2 and x = -1/3 after using the quadratic formula.
Learn more about quadratic equations here:
brainly.com/question/2263981
#SPJ2